The Comparative Fertility of the Native and the Foreign-Born Women in New York, Indiana, and Michigan - Spengler, Joseph J. (Quarterly Journal of Economics, 1931)
Introduction, 460. — Birth registration introduced after 1850 but generally unsuccessful in the United States, 460. — Census and registration returns in New York, 465. — Birth registration in Indiana, 470. — Census and birth registration returns in Michigan, 472. — Conclusions, 482.